Implementasi Indeks Pertanaman 400 untuk Meningkatkan Produksi Padi Indonesia: Studi Kasus Kabupaten Sukoharjo - Fitrianingrum Kurniawati; Andi Muhammad Syakir; Baran Wirawan; Ahmad Junaedi; Muhammad Prama Yufdy; Dwi Rachmina; Sabrina Aulia Zahra; Ahmad Ramadhani; Gusmaini Gusmaini; Destika Cahyana (Institut Pertanian Bogor, 2025)
Sukoharjo Regency, Central Java, is an example of successfully implementing rice planting using the Planting Index 400 (IP-400). This study aimed to analyze the difference in total farming costs between IP-400 and non-IP-400 rice varieties and their sustainability. Farmers in Sukoharjo have succeeded in planting rice three to four times a year in rice fields with technical irrigation. This activity was carried out in five stages, i.e. 1) a Discussion with the Head of the Sukoharjo Regency Agriculture and Fisheries Service, Central Java and his staf; 2) Focus Group Discussion (FGD) with the Head of the Sukoharjo Regency Agriculture and Fisheries Service, Heads of Farmer Groups and their members, Delegates from the Directorate General of Food Crops, Ministry of Agriculture, as well as related parties; 3) Field visits to rice seed entrepreneurs; 4) Field visits to